1996
DOI: 10.1089/hum.1996.7.14-1771
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Co-Stimulatory Molecules by Tumor Cells Decreases Tumorigenicity but May Also Reduce Systemic Antitumor Immunity

Abstract: Many tumor cells do not express co-stimulatory molecules, and this may account, in part, for their poor ability to stimulate T cells directly. One strategy to enhance immune recognition would be to express such molecules on the tumor cell. Here, we show that expression of a member of the B7 family of co-stimulatory molecules by CMT93 murine colorectal tumor or 1735 murine melanoma cells resulted in a local antitumor response in immunocompetent mice. The antitumor effect was diminished in athymic nude mice, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…These mice showed a significantly increased level of protection compared with mice which had been given parental CMT93 cells initially and had tumours that required excision ( Figure 5) (P Ͻ 0.02, stratified log rank test). In the group which had received a primary inoculation of CMT93 B7-1 cells, there was a tendency to improved protection compared with mice which had primary parental tumours but, consistent with our previous findings, 20 analysis of data from independent repeated experiments failed to indicate that this increase was significant. Similarly, mice which had been injected initially with CMT93 IL-12 cells (not coexpressing B7-1) also showed a trend to enhanced protection, but this did not reach a level of significance.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These mice showed a significantly increased level of protection compared with mice which had been given parental CMT93 cells initially and had tumours that required excision ( Figure 5) (P Ͻ 0.02, stratified log rank test). In the group which had received a primary inoculation of CMT93 B7-1 cells, there was a tendency to improved protection compared with mice which had primary parental tumours but, consistent with our previous findings, 20 analysis of data from independent repeated experiments failed to indicate that this increase was significant. Similarly, mice which had been injected initially with CMT93 IL-12 cells (not coexpressing B7-1) also showed a trend to enhanced protection, but this did not reach a level of significance.…”
Section: Resultssupporting
confidence: 88%
“…18,19 CMT93 murine colorectal tumour is of relatively low intrinsic immunogenicity and previously we demonstrated that expression of B7-1 prevented the growth of the primary tumour, but did not produce a significant increase in the level of systemic immunity, relative to that evoked by the parental tumour. 20 Conversely, expression of B7-1 or B7-2 in another tumour, K1735 murine melanoma, a moderately immunogenic tumour, resulted in retarded growth of the primary tumour, but the systemic immunity elicited was weaker than that generated by the parental tumour. 20 Recently, the ability of B7-expressing tumours to elicit systemic immunity was suggested to be dependent not only on direct antigen presentation to T cells by tumour cells, but also on crosspriming of T cells by host professional APCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, attempts to enhance tumor immunogenicity have included transfection of tumor cells with cDNA for the B7.1 costimulatory molecule. Several studies report a decrease in tumorigenicity following transfection of tumors with B7.1 7,28 , whereas others have described progressive growth of B7.1 ( + ) tumors. 6,35 These conflicting results may have two explanations.…”
mentioning
confidence: 99%
“…Construction of B7.1 ( + ) tumor vaccines in some models has resulted in protection against subsequent wild -type tumor challenge. 7,12,28 Unfortunately, in a clinical model, the presence of a pre -existing tumor burden makes this approach less attractive and a direct treatment model more appealing. B7.1 is one of two known ligands for the CD28 and CTLA -4 receptors on immune effector cells.…”
mentioning
confidence: 99%